Analisis Ion Nitrit (NO₂⁻) pada Aplikasi Silika Gel Termodifikasi GPTMS-DMA secara Kromatografi - Isra Hayati; Budhi Oktavia (Lembaga Yasin AlSys, 2025)
The limited research on the use of modified silica gel as a stationary phase in ion chromatography forms the basis of this study, particularly for the analysis of nitrite ions (NO₂⁻), which are toxic and pose risks to both human health and the environment. This study aims to apply glycidoxypropyltrimethoxysilane–dimethylamine (GPTMS–DMA) modified silica gel as a stationary phase in the analysis of nitrite ions. A quantitative experimental method was used, employing nitrite ion samples at concentrations of 100 ppm, 200 ppm, and 300 ppm. The analysis was conducted using a High Performance Liquid Chromatography (HPLC) system equipped with a UV detector and carbonate-based eluents consisting of Na₂CO₃ and NaHCO₃ at concentrations of 0.1 M, 0.05 M, and 0.01 M. The results showed that 0.1 M Na₂CO₃ produced the sharpest chromatogram peaks, highest intensity, and the most stable baseline. The resulting regression equation was y = 0.0093x + 0.1533 with a determination coefficient R² = 0.9939, indicating excellent linearity. The Limit of Detection (LOD) was 33.47 ppm, and the Limit of Quantification (LOQ) was 111.56 ppm, demonstrating adequate sensitivity. The study concludes that GPTMS–DMA silica gel effectively enhances the sensitivity and selectivity of nitrite ion analysis and shows strong potential for further development in the analysis of other inorganic ions.